The Conventional Langmuir Trough Technique as a Convenient Means to Determine the Solubility of Sparingly Soluble Surface Active Molecules Case Study Cholesterol - Savva, Michalakis (Colloids and surfaces. A, Physicochemical and engineering aspects, 2008)
The feasibility of a method based on mass preservation [G. Schwarz, J. Zhang, Chem. Phys. Lipids, 110 (2001) 35-45] to determine the solubility of Cholesterol in water from monomolecular films on air/water interface was investigated. Using a mass balance equation, it was found that Cholesterol undergoes an exponential desorption at very low surface pressures followed by an almost linear desorption into the subphase at higher surface pressures until monolayer collapse. Processing of the surface pressure measurements as a function of trough area in accord with the theory, enabled the accurate determination of the molecular dimensions of Cholesterol as a function of surface pressure. Slight modification of the theory enabled accurate quantification of the surface pressure-independent apparent solubility of Cholesterol and the amount of Cholesterol desorbed into the subphase as a function of surface pressure, in the nanomolar range